Des identités (dé)politisées ? Les enjeux de catégorisation des Nubien.ne.s en Égypte - Mérième Ihsan (L’Année du Maghreb)
In line with works that study the way the state manages its cultural groups, this article aims to account for the complexity of the process of category construction on which the narratives and representations of several actors are intertwined. Reversing a dichotomous vision of the state vs. the Nubians, the article aims to highlight the heterogeneity of actors (the state, researchers, activists, associative leaders, etc.) who participate in the categorisation process. Using this perspective, it examines this process at the intersection of the issues of politicisation and depoliticisation, namely, the deconflicted readings, disseminated in a globalised context, giving rise to processes of politicisation with variable geometry. “Variable geometry” because these processes depend on the different interactions between the various actors, the circulation of narratives and academic works, and the setting-up of spaces that are not all necessarily political but that promote awareness and reinforce the identification of individuals. As we will see, the processes of categorisation are part of a grey zone that oscillates between recognition and denial, between political and “apolitical”, giving rise to strategies of appropriation, negotiation and contestation. To this end, the article first analyses the way in which interest in heritage issues becomes an instrument of homogenisation, the aim of which is to reduce conflict with the state. It then examines ethnological studies of the Nubian population and their role in the dissemination of a folkloric and sometimes essentialist image of the population. The article then traces the attempts at politicisation through the appropriation of political categories (such as “indigenous” and “minority”) in order to become part of a global discourse. While this discourse emerges among some activists from the 2000s onwards, researchers also contribute further to these processes of politicisation by making use of these categories in their work.